Valoración de las actividades antropogénicas establecidas en tres pisos bioclimáticos de la zona noroccidental de la Provincia de Cotopaxi - Rojas Rea, Oswaldo Daniel (2021)
In the present research study, the assessment of anthropogenic activities established on three bioclimatic floors of the northwestern area of the Cotopaxi province was carried out, for this the diagnosis of the current situation of the bioclimatic floors of the humid forest was initiated, with the purpose of establish the anthropogenic activity identified as critical within the three bioclimatic floors. The research was carried out through a non-experimental design that was applied in a transversal way, bibliographic and descriptive methods were applied, jointly applied with the techniques of surveys, observation, field trips, SWOT matrix that allows to identify the strengths, threats, opportunities and weaknesses. The results achieved allowed the identification of anthropogenic activities with a percentage of 50% destined to agriculture, 35% to livestock and 15% activities directed to the tourism sector, then they were grouped by sectors considering all the actions that may cause an environmental impact, they were considered three environmental, physical, biological and cultural aspects. Immediately, a subjective assessment of the environmental impacts of the activities was carried out, within this assessment criterion such as magnitude and importance were considered. In general, it is observed that, through the analysis carried out, the environmental element that was considered as affected was the flora and fauna component. The activities that generate the greatest negative impacts are within the agricultural sector. Being important to establish training aimed at sustainability, and the ecological balance of these areas of great importance.